O przekładach literatury polskiej w Czechach i czeskiej w Polsce. Komentarz do bibliografii przekładów w 2014 roku - Żygadło‑Czopnik, Dorota (Przekłady Literatur Słowiańskich, 2015)
On translating Polish literature in the Czech Republic and Czech literature in Poland. Commentary on the 2014 bibliography The history of Polish‑Czech dealings is long. There is no doubt that the year 1989 brought epochal changes in Polish‑Czech relations. Only then did the Czechs and Poles become rightful neighbours. Territorial disputes are a nonissue and the two countries are connected to each other with mutual affection of the cultural and political elite. Czech‑Polish relations are the best they have been in over a thousand years. This publication, although small in scale, is intended to provide a full picture of the cultural and linguistic relationship between the two nations for the year 2014. It can be viewed as a valuable contribution to this issue. The bibliography is divided into two parts, where the first includes, The bibliography of the translated works of Polish literature in the Czech Republic in 2014, and the second one includes, The bibliography of the translated works of Czech literature in Poland in 2014. Both parts include translated literature. The bibliography is devoted not only to books, but also takes into account periodicals and websites. The ultimate goal of the whole project was to provide both the experts and readers, through the series „Slavic Literature Translations”, with a comprehensive list of translated works of Polish and Czech literature published in Poland and the Czech Republic in the year 2014. Key words: commentary, bibliography, translation, Polish and Czech literature